UNDERSTANDING OF JUSTICE IN PEOPLE WITH DIFFERENT LEVELS OF SENSITIVITY TO ITS VIOLATION - Adamyan, A. A. (Modern Psychology, 2019)
The article discusses relationships between justice sensitivity and common attitudes to justice. Justice sensitivity is understood as a person’s willingness to perceive injustice and his emotional, cognitive and behavioral responses to it. Study participants (N=98; mean age=18.6, SD = 1.2) gave associations to the notion of "justice" and completed Justice Sensitivity Inventory. Associations were grouped according to the categories of common attitudes to justice that are distinguished for Russian society. Regardless of the level of justice sensitivity, the most common category of association is “the ability to believe a person”. Subjects with high justice sensitivity from victim’s perspective associated justice with morality more often, and with objectivity less often than the group with low victim justice sensitivity. For subjects with high justice sensitivity from witness’s perspective, justice is also less associated with the notion of objectivity.